Clinical implications of molecular subtyping in bladder cancer. Issue 4 (July 2019) - Satyal, Uttam; Sikder, Rahmat K.; McConkey, David; Plimack, Elizabeth R.; Abbosh, Philip H.
Abstract : Purpose of review: The purpose of this review is to examine and evaluate similarities and differences in bladder cancer expression subtypes and to understand the clinical implications of the molecular subtyping. Recent findings: Four independent classification systems have been described, and there are broad similarities among the subtyping callers. Two major subtypes have been identified, that is, luminal and basal, with underlying subcategories based on various distinct characteristics. Luminal tumors generally bear a better prognosis and increased survival than basal tumors, although there is subtle variation in prognosis among the different subtypes within the luminal and basal classifications. Clinical subtyping is now commercially available, although there are limitations to its generalizability and application. Summary: Expression subtyping is a new method to personalize bladder cancer management. However, there is probably not sufficient evidence to incorporate use into current standards-of-care. Validation cohorts with clinically meaningful outcomes may further establish the clinical relevance of molecular subtyping of bladder cancer. Additionally, genetic alterations in bladder cancer may 'color' the interpretation of individual tumors beyond the expression subtype to truly personalize care for bladder cancer.